Modeling spatial spread of west nile virus and impact of directional dispersal of birds - Rongsong Liu; Jiangping Shuai; Jianhong Wu; Huaiping Zhu (Mathematical Biosciences and Engineering)
A patchy model for the spatial spread of West Nile virus is formulated and analyzed. The basic reproduction number is calculated and compared for different long-range dispersal patterns of birds, and simulations are carried out to demonstrate discontinuous or jump spatial spread of the virus when the birds' long-range dispersal dominates the nearest neighborhood interaction and diffusion of mosquitoes and birds.